ELECTRONIC SUPPORT SYSTEM OF NORMATIVE LEGAL BASE OF DISTANCE LEARNING SYSTEM - Pyetukhova Л.Є.; Osipova, H.B. (Journal of Information Technologies in Education (ITE), 2010)
Information-communication technologies in the system of distance learning, their contents, place and functions in the educational process were analyzed in the paper. System of electronic support of legal base of distance learning system created at Kherson State University is reviewed. There was made a conclusion, based on the experience analysis of distance technologies use, about a necessity to improve legal base of distance learning and create also a united information-educational space of Higher Educational Establishments of Ukraine.